Solution-based manufacturing of 2D materials for memristive device applications - Kijeong Nam; Gwang Ya Kim; Dongjoon Rhee; Hyesung Park; Deep Jariwala; Joohoon Kang (International Journal of Extreme Manufacturing)
Two-dimensional (2D) materials have attracted significant attention as resistive switching materials for two-terminal non-volatile memory devices, often referred to as memristors, due to their potential for achieving fast switching speeds and low power consumption. Their excellent gate tunability in electronic properties also enables hybrid devices combining the functionality of memory devices and transistors, with the possibility of realizing large-scale memristive crossbar arrays with high integration density. To facilitate the use of 2D materials in practical memristor applications, scalable synthesis of 2D materials with high electronic quality is critical. In addition, low-temperature integration for complementary metal oxide semiconductor (CMOS) back-end-of-line (BEOL) integration is important for embedded memory applications. Solution-based exfoliation has been actively explored as a facile, cost-effective method for the mass production and low-temperature integration of 2D materials. However, the films produced from the resulting 2D nanosheet dispersions exhibited poor electrical properties in the early stages of research, thereby hindering their use in electronic devices. Recent progress in the exfoliation process and post-processing has led to significant improvements in the electronic performance of solution-processed 2D materials, driving increased adoption of these materials in memristor research. In this review article, we provide a thorough overview of the progress and current status of memristive devices utilizing solution-processed 2D resistive switching layers. We begin by introducing the electrical characteristics and resistive switching mechanisms of memristors fabricated with conventional materials to lay the groundwork for understanding memristive behavior in 2D materials. Representative solution-based exfoliation and film formation techniques are also introduced, emphasizing the benefits of these approaches for obtaining scalable 2D material films compared to conventional methods such as mechanical exfoliation and chemical vapor deposition. Finally, we explore the electrical characteristics, resistive switching mechanisms, and applications of solution-processed 2D memristive devices, discussing their advantages and remaining challenges.